Geometric Properties of Landscapes - H.D. Tjia (Journal of Mathematical and Fundamental Sciences, 1965)
Abstract. Quantification of landforms has been executed for most watershed elements and adjacent slopes and some concerning mountains and distribution pattern of land and water. Almost all watershed characteristic are based on the system of stream ordering. Empirically certain statistical relations of landscape elements have been proven to exist beyond doubt like  the laws of stream numbers, stream lengths, stream slopes, drainage basin areas, contributing areas; also: constant of channel maintenance; drainage density and texture ratio; relief ratio; hypsometric integrals for drainage basins and mountains; frequency distribution of stream lengths; maximum valley side slopes. Furthermore, interesting results may be expected from the concepts of geometrical similarity of drainage basins and the distribution pattern of land and water. The good to excellent quality of Indonesian topographic maps invite an immediate investigation of drainage density and texture ratio; hypsometric integral, maximum valley side slopes, and relief ratio in order to obtain quantitative proofs in distinguishing landforms as products of humid tropics from those of the temperate humid/dry climates. Ichtisar. Sifat-sifat geometri dari bengtangalam telah diukur setjara kwantitas, seperti untuk kebanjakan unsur-unsur daerah aliran dan beberapa mengenai gunung dan penjebaran dari daratan dan air. Hampir semua sifat daerah aliran didasarkan atas suatu sistim tata-atur aliran (stream ordering). Dalam praktek telah dapat dipastikan beberapa hubungan antara unsur-unsur bentangalam masing-masing, seperti hokum-hukum djumlah sungai, pandjang sungai, terdjun sungai, luas daerah aliran, 'contributing areas'; 'constant of channel maintenance'; 'drainage density and texture ratio'; 'relief ration'; 'hypsometric integral' untuk daerah aliran dan untuk gunung; 'frequency distribution' dari pandjang sungai; maksimum dari lereng lembah. Selandjutnya masih dapat diharapkan hasil-hasil jang menarik dari konsepsi 'geometrical similarity' dari daerah aliran serta dari teori pola penjebaran daratan dan air. Peta-peta topografi Indonesia jang ketelitiannja sangat baik sudah memungkinkan penjelidikan geomorfologi kwantitatif disini. Sebagai permulaan penjelidikan mengenai 'drainage density and texture ratio', hypsometric integral', lereng lembah maksimum dan 'relief ratio' dapat dilakukan guna memperoleh angka-angka untuk membeda-bedakan bentangalam sebagai hasil dari iklim tropika lembab dan jang dibentuk oleh iklim sedang lembab kering.